Weak solutions of the transmission problem in anti‐plane Cosserat elasticity. Issue 6 (3rd September 2015) - Atroshchenko, E.; Potapenko, S.
Abstract : In this paper the authors prove the existence of weak solutions for the inclusion problem in anti‐plane Cosserat elasticity in Sobolev space setting, and for the corresponding systems of boundary integral equations. Abstract : In this paper we prove the existence of weak solutions for the inclusion problem in anti‐plane Cosserat elasticity in Sobolev space setting, and for the corresponding systems of boundary integral equations.